2010
DOI: 10.1186/1471-2377-10-53
|View full text |Cite
|
Sign up to set email alerts
|

An excess vessel in the posterior part of the human cerebral arterial circle (CAC): a case series

Abstract: BackgroundAs a continuation of the previous findings in human fetuses, accidental finding of an accessory vascular component in the posterior part of CAC of human adult cadavers inspired the authors to present and compare its posterior part configuration.Case presentationExamination was carried out on brains of 48 human adult cadavers, routinely dissected at the Institute of Forensic Medicine. The aberrant vessel in the posterior part of four CACs was discovered.Vascular components of the posterior segment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…The "typical" circle of Willis was defined with respect to its components as a closed circuit in which fluid may circulate from any entrance point back to the same point with all vessels more than 1 mm in external diameter and with no excess vessels (Kayembe et al, 1984). Variable five vascular components in the circle posterior part are previous described in fetuses and adults (Vasović, 2004;Vasović et al, 2010). Many authors wide world have studied about the length, diameter and anomalies in the origin of vascular components of the circle of Willis and found that the parameters in different geographical limits were different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "typical" circle of Willis was defined with respect to its components as a closed circuit in which fluid may circulate from any entrance point back to the same point with all vessels more than 1 mm in external diameter and with no excess vessels (Kayembe et al, 1984). Variable five vascular components in the circle posterior part are previous described in fetuses and adults (Vasović, 2004;Vasović et al, 2010). Many authors wide world have studied about the length, diameter and anomalies in the origin of vascular components of the circle of Willis and found that the parameters in different geographical limits were different.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the circle of Willis may be critical because anomalies and hypoplasia of the circle of Willis are frequent (Merkkola et al, 2006). Anomalies found in a pattern of the posterior part of the circle of Willis result due to persistence of vessels that normally disappear or disappearance of normal vessels (Vasović, 2004;Kapoor et al, 2008;Vasović et al, 2010). Although the association of variations and aneurysms had been used as an argument in favor of a congenital theory of aneurismal development, it should be interpreted in terms of the hemodynamic stress caused by variations (Kayembe et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…According to this opinion, we considered that ICoA is a CVBA. The presence of this supernumerary vessel in the CAC was proved in 7/200 fetuses (16), and 4/48 adult cadavers (17). The coexistence of the PPTA and ICoA in this and previous cases (18), or the PPTA and another CVBA (14,24), could be related to an underlying embryologic dysgenesis or a common insult resulting in vascular maldevelopment during the first several gestational weeks.…”
Section: █ Discussionmentioning
confidence: 54%
“…In this, as well as in previous cases (16)(17)(18), the cerebral arterial circle (CAC) with an ICoA connecting two right PCAs can be compared with a decagon. We think that the right PCA of basilar origin is a continuation of primitive longitudinal neural artery on this side, while the PCA of carotid origin and ICoA were branches of a caudal end of primitive ICA.…”
Section: █ Discussionmentioning
confidence: 93%
“…This plexus may persist postnatally as the single intermediate communicating artery, which explains the origin of the vascular anastomosis joining the doubled PCA. The persistence of the vestigial vessels of the internal carotid and vertebrobasilar systems or the carotid-basilar anastomoses explains the cases of vascular duplication and fenestration (14,16).…”
Section: Discussionmentioning
confidence: 99%